THE IMPLEMENTATION OF INTELLECTUAL PROPERTY DISPUTE RESOLUTION THROUGH MEDIATION & ARBITRATION - Sidik, Jafar; Rozali, Asep; Sulistianingsih, Dewi (Masalah-Masalah Hukum, 2023)
This article aims at determining, describing, and analyzing the application of intellectual property rights through mediation & arbitration from the perspective of Indonesian law and its practice in the Arbitration Regulations of the Indonesian National Arbitration Board. Intellectual Property dispute resolution among the disputing parties by mediation and arbitration (out-of-state court settlement) has not been effective because of limited and lack of socialization from the Government or mediation and arbitration institution. The resolution of IPR disputes has not been effective, this is evident from the results of discussions with the DJKI and the West Java Kanwilkumham, which are still few IPR cases that have been registered to be resolved. Likewise, very few IPR cases have been submitted to the Dispute Resolution Institution.